Modelling and assessment of the contribution of demand response and electrical energy storage to adequacy of supply. (September 2015) - Zhou, Yutian; Mancarella, Pierluigi; Mutale, Joseph
Abstract: Demand response (DR) and electrical energy storage (EES) are key attributes within the context of smarter and more sustainable power systems. However, little work has so far systematically investigated the reliability implications of deploying DR and EES at the system level, including the impacts of characteristics such as the energy payback and flexibility of DR or the capacity and efficiency of EES. Nevertheless, this is fundamental to address the questions as to how DR and EES affect system reliability and whether and to what extent they could displace generation capacity while maintaining sufficient system adequacy. Therefore, this paper aims at developing a general framework to evaluate the contribution of DR and EES to adequacy of supply by specifically modelling and analysing their operational flexibility parameters and constraints. Specific studies are run using sequential Monte Carlo simulation that allows capturing the relevant inter-temporal constraints. The results suggest that, given a prevailing generation portfolio, DR and EES could reduce the frequency and cumulative duration of interruptions, although these might become more severe. The amount of generation that could be displaced is then quantified, which is found to be less than the peak reduction provided by DR and EES while preserving system adequacy. The models and findings of this work are thus critical to quantitatively inform the energy policy debates about the potential of DR and EES to provide system capacity and participate in relevant markets. Highlights: We model specifically the operational flexibility and constraints of DR and EES. DR and EES contribute to adequacy of supply by reducing system peak demand. Energy payback deteriorates the reliability performance of individual interruptions. Decommissioned generation must be less than the peak reduction owing to DR and EES.